Capital Requirements for Over-the-Counter Derivatives Central Counterparties - Lin, Li (IMF Working Papers; Working Paper ;, 2013)
The central counterparties dominating the market for the clearing of over-the-counter interest rate and credit derivatives are globally systemic. Employing methodologies similar to the calculation of banks' capital requirements against trading book exposures, this paper assesses the sensitivity of central counterparties' required risk buffers, or capital requirements, to a range of model inputs. We find them to be highly sensitive to whether key model parameters are calibrated on a point-in-time versus stress-period basis, whether the risk tolerance metric adequately captures tail events, and the ability-or lack thereof-to define exposures on the basis of netting sets spanning multiple risk factors. Our results suggest that there are considerable benefits from having prudential authorities adopt a more prescriptive approach to for central counterparties' risk buffers, in line with recent enhancements to the capital regime for banks.